An epidemiological study of occupational bladder tumours in the dye industry of Japan. Issue 3 (August 1975) - Tsuchiya, K; Okubo, T; Ishizu, S
Abstract : This report studies 100 cases of occupational bladder cancer which were reported between 1949 and 1970 by large companies producing dye. It is estimated that in fact a great many more than 100 cases may have developed during the 56 years from 1914 to 1970, as this period corresponds with the beginning of dye production to the termination of benzidine and beta-naphthylamine manufacture in Japan. New cases of occupational bladder tumour should diminish significantly in the future in Japan on account of the prohibition of the production of beta-naphthylamine and benzidine. However, it is important to follow-up continuously workers who have been exposed to these amines. In Japan no cases of occupational bladder tumours from the rubber industry have been reported. It is emphasized that prospective epidemiological studies are required not only in the rubber industry but also in other industries where amines may constitute an occupational hazard.